Pengaruh Green Marketing, Inovasi Produk, dan Brand Image Terhadap Minat Beli - Sukma P, Fika Riskiana; Susanto, Susanto; Hutami, Lusia Tria Hatmanti (Jurnal Ilmiah Manajemen Kesatuan, 2021)
This study aims to determine the effect of Green Marketing, Product Innovation, and Brand Image on Buying Interest in KFC Consumer UST FE Student. Many female students currently buy KFC products. In Indonesia itself, there are various kinds of well-known fast food restaurants in this community such as McDonald's, A&W, Richeese Factory, Hokben, and others. Sometimes we get confused between these restaurants. That's why in this study, researchers want to know what factors influence female students. Researchers narrow down three variables, Green Marketing, Product Innovation, and Brand Image. This research uses quantitative research and selects 100 people (male & female, 18-26 years old, management or accounting study program and purchasing KFC products) as research subjects. Researchers used the SPSS application to test the results of the study. The results showed that the most influential factor in influencing product purchase intention was Green Marketing, followed by Brand Image, and the last one that had the least influence was Product Innovation. Keywords: Green Marketing, Product Innovation, Brand Image, Purchase Interest.